Institutional vacuum in Sardar Sarovar Project: farming "rules-of-the-game? - Talati, Jayesh; Shah, Tushaar (2004)
Few large irrigation projects in India have been as elaborately planned as the Sardar Sarovar Project (SSP), incorporating as it did the lessons of decades of irrigation project design and management. The project was to blaze a new trail in farmer-participatory irrigation project design and management with water user associations building their own distribution systems. However, as it unfolds, the institutional reality of the project is vastly different from its plans. If SSP is to chart a different course from scores of earlier large irrigation projects, it must invent and put into place new rules of the irrigation management game.